2004
DOI: 10.1021/jf034814l
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Glycemic Index of Brazilian Pine (Araucaria angustifolia) Seeds

Abstract: The seeds of Parana pine (Araucaria brasiliensis syn. Araucaria angustifolia), named pinhão, are consumed after cooking and posterior dehulling, or they are used to prepare a flour employed in regional dishes. Native people that live in the South of Brazil usually consume baked pinhão. As a result of cooking, the white seeds become brown on the surface due to the migration of some tinted compounds present in the seed coat. In this work, the proximate composition, minerals, flavonoids, and glycemic index (GI) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
127
3
32

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(173 citation statements)
references
References 19 publications
11
127
3
32
Order By: Relevance
“…In a previous study, Cordenunsi et al (2004) showed that the native pinhão starch has interesting structural and functional characteristics as a new source of starch; the granules had a low protein (3%) and lipids content (1.3%) and an amylose content of 26%. The objective of this study was to determine the effect of chemical modifications (acid hydrolysis) on the technological functional properties of pinhão starch.…”
Section: Paste Freeze-thaw Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Cordenunsi et al (2004) showed that the native pinhão starch has interesting structural and functional characteristics as a new source of starch; the granules had a low protein (3%) and lipids content (1.3%) and an amylose content of 26%. The objective of this study was to determine the effect of chemical modifications (acid hydrolysis) on the technological functional properties of pinhão starch.…”
Section: Paste Freeze-thaw Stabilitymentioning
confidence: 99%
“…The seed of this tree, harvested from April to August, is known as pinhão, and it is most commonly eaten after being cooked and peeled. Pinhão is also used as raw flour as an ingredient for several dishes, and is considered a source of starch (~36%), dietary fiber, magnesium and copper, besides producing a low glycemic index after its consume (CORDENUNSI et al, 2004). Although nutritional and technological aspects of pinhão are scarce in the scientific literature, recent studies suggest that the Araucaria seed is a potential alternative source of starch extraction for industrial purposes (CORDENUNSI et al, 2004;BELLO-PEREZ et al, 2006;STAHL et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Residual pinhão coats, which represent about 20% of the weight (Conforti & Lupano, 2008;Cordenunsi et al, 2004), has also been attracting interest due to its antioxidant properties and potential biological activity. da Mota et al (2014) obtained methanolic extracts from the shell and pulp of A. angustifolia seeds and identified in both extracts the presence of molecules with free radicals-trapping ability (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…According to the survey on the distribution of Araucaria angustifolia in Brazil by Hueck (1953Hueck ( , 1966, there is no evidence of the natural distribution of this tree in the lowlands of Rio Grande do Sul. It is therefore possible that this occurrence is due to post-Columbian settlers, which would have planted these trees on their lowland farms for wood as well as for the nutrient supply provided by the seeds (Cordenunsi et al 2004;Bello-Perez et al 2006). First settlers from Portugal arrived to the region during the early 19 th century (Corrêa 2013).…”
Section: Introductionmentioning
confidence: 99%